Are institutional innovations helpful in reducing transaction costs? An empirical analysis of agri-based Farmer Producer Companies (FPCs) in Kerala, India - Divya, KM; Kumar, D Suresh; Vidhyavathi, A; Babu, Suresh Chandra; Uma, K; Kannan, Balaji; Kalarani, MK (Horizon E-Publishing Group, 2024)
Transaction costs are incurred while conducting a transaction through an exchange in the open market. New institutional economics focuses on transaction costs and the institutions involved in their reduction. This study compares the transaction costs incurred by Farmer Producer Company (FPC) members and non-members in Kerala and identifies the factors affecting these transaction costs. The study revealed no significant difference in the transaction costs incurred by FPC members and non-members. This was mainly due to the significant and higher opportunity cost of time spent on information and decision-making by FPC members compared to non-members, which surpassed the lower costs incurred for selling their farm produce by FPC members compared to non-members. Based on this study, we recommend that FPCs concentrate more on the bottom-up collectivization of individual farmers to form large business organizations that facilitate market access for small and marginal farmers and reduce transaction costs.